Cell wall mannoprotein of Candida albicans induces cell cycle alternation and inhibits apoptosis of HaCaT cells via NF-κB signal pathway. (October 2017) - Han, Yang; Jiang, Hang-hang; Zhang, Yu-jing; Hao, Xing-jia; Sun, Yu-zhe; Qi, Rui-qun; Chen, Hong-duo; Gao, Xing-hua
Abstract: Candida albicans ( C. albicans ) is a commensal organism in human and a well-known dimorphic opportunistic pathogenic fungus. Though plenty of researches on the pathogenesis of C. albicans have been performed, the mechanism is not fully understood. The cell wall components of C. albicans have been documented to play important roles in its pathogenic processes. To further study the infectious mechanism of C. albicans, we investigated the potential functional role of its cell wall mannoprotein in cell cycle and apoptosis of HaCaT cells. We found that mannoprotein could promote the transition of cell cycle from G1/G0 to S phase, in which Cyclin D1, CDK4 and p-Rb, the major regulators of the cell cycle progression, showed significant upregulation, and CDKN1A (cyclin dependent kinase inhibitor 1A (p21)) showed significant downregulation. Mannoprotein also could inhibit apoptosis of HaCaT cells, which was well associated with increased expression of BCL2 (Bcl-2). Moreover, mannoprotein could increase the phosphorylation levels of RELA (p65) and NFKBIA (IκBα), as the key factors of NF-κB signal pathway in HaCaT cells, suggesting the activation of NF-κB signal pathway. Additionally, a NF-κB specific inhibitor, PDTC, could rescue the effect of mannoprotein on cell cycle and apoptosis of HaCaT cells, which suggested that mannoprotein could activate NF-κB signal pathway to mediate cell cycle alternation and inhibit apoptosis. Highlights: Mannoprotein of C. albicans promoted the transition of cell cycle in HaCaT cells. Mannoprotein inhibited apoptosis of HaCaT cells. Mannoprotein activated NF-κB signal pathway to impact cell cycle and apoptosis.